1992
DOI: 10.1039/c39920000740
|View full text |Cite
|
Sign up to set email alerts
|

Motion in solid organotin(IV) coordination polymers: a two-dimensional exchange magic angle spinning 13C NMR study

Abstract: Solid-state 13C CP MAS NMR studies of compounds [(Me3Sn),M(CN),], with M = Fe, Ru and Os, using variable temperature, show that the trigonal bipyramidal arrangements a t Sn are undergoing internal rotation about the N-Sn-N axes with lifetimes of the order of 0.5 s a t moderately lowered temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(80 citation statements)
references
References 7 publications
2
78
0
Order By: Relevance
“…The phenyl rings occupying the positions of TP-3 and of PT-4 formed by the Sn(l) and Sn(2) atoms, respectively, are crystallographically equivalent around room temperature owning to rapid rotation about their individual trigonal axes. This conclusion is further substantiated by the previous solid state 13 C NMR [15] and 2D-EXSY [17] studies which confirmed the rapid rotation of the alkyl groups (on the NMR time scale) about their individual trigonal axes. It is, also, observed that the angles of C(6)eCu (3) Table 4.…”
Section: Resultssupporting
confidence: 69%
“…The phenyl rings occupying the positions of TP-3 and of PT-4 formed by the Sn(l) and Sn(2) atoms, respectively, are crystallographically equivalent around room temperature owning to rapid rotation about their individual trigonal axes. This conclusion is further substantiated by the previous solid state 13 C NMR [15] and 2D-EXSY [17] studies which confirmed the rapid rotation of the alkyl groups (on the NMR time scale) about their individual trigonal axes. It is, also, observed that the angles of C(6)eCu (3) Table 4.…”
Section: Resultssupporting
confidence: 69%
“…When proton positions were not available from X-ray diffraction results, an average C-H bond length of 1.08 A ˚was set, with a tetrahedral arrangement for methyl bonds. We should point out that reorientation motions of protons and methyl groups 19,20 around the tin atom average the shielding effect due to Sn-CH 3 bonds; hence the accuracy in the C-H distance should not be critical.…”
Section: Methodsmentioning
confidence: 99%
“…Although solid-state 1 H and 2 H NMR spectroscopy has been used to study the dynamics of the water molecules in KFCT, 45,[57][58][59] solid-state NMR has yet to be used to study the solid ferrocyanide anion directly. Thus, we have used 13 C and 15 N magic-angle spinning, MAS, NMR spectroscopy, in combination with single-crystal and powder X-ray diffraction, to gain an understanding of the suprisingly complex polymorphism of KFCT.…”
Section: Introductionmentioning
confidence: 99%
“…
The polymorphism of bulk powder samples of potassium ferrocyanide trihydrate (K 4 Fe(CN) 6 • 3H 2 O, KFCT) has been studied using 1 H, 13 C, and 15 N NMR spectroscopy in combination with X-ray diffraction. At room temperature, KFCT typically crystallizes in a monoclinic C2/c form, which converts irreversibly to a monoclinic Cc form upon cooling below -25 °C.
…”
mentioning
confidence: 99%